Jane and the man of the cloth : being the second Jane Austen mystery - Barron, Stephanie (New York : Bantam Books, 1997)
Jane Austen and her family are looking forward to a peaceful summer vacation in the seaside village of Lyme Regis. When a man is found hanged from a makeshift gibbet by the sea, his death is linked to "the Reverend", the notorious ringleader of the midnight smuggling trade. Jane, who can never resist a puzzle, is determined to solve this one.
Library Journal.
Pub Weekly.
School Library Journal.
Adult
Keywords: Austen, Jane, -- 1775-1817 -- Fiction; Austen, Jane, -- 1775-1817 -- Fiction; Mystery fiction; Great Britain -- Fiction; Great Britain -- Fiction